BIOREMEDIATION OF CRUDE OIL CONTAMINATED SEAWATER WITH THE APPLICATION OF BIOSURFACTANT AND BIOSTIMULATION - Zulkifliani Zulkifliani; Atiyah F F Yumna; Subagiyo Subagiyo (Testing Center for Oil and Gas LEMIGAS, 2018)
Petroleum is one of the pollutant sources that can be found in the oceans and has a negative impact onthe marine ecosystem. Special conditions are needed to reduce the pollutant, one of the processes that occursis biodegradation, which is the process of degradation of petroleum hydrocarbon components by the activityof microorganisms so that the marine ecosystem returns to normal. Remediation of seawater contaminatedwith petroleum through the application of biosurfactants and biostimulation is one way to increase theeffectiveness of petroleum biodegradation. To examine these aspects laboratory-scale experiments werecarried out using basic seawater media which added oil pollutants. There are four treatments: P0 (basicmedia without the addition of biosurfactant and nutrients), P1 (addition of biosurfactant), P2 (additionof biosurfactant and nutrients), and P3 (addition of nutrients). The results of observations for 21 daysof incubation showed that the addition of biosurfactant treatment did not show a signifi cant increase110in biodegradation. Signifi cant increase in biodegradation occurs in the treatment with the addition ofbiostimulants and more degradation if biostimulation is combined with biosurfactant.